Capitalism : a global history - Beckert, Sven (Penguin Press, an imprint of Penguin Random House LLC, 2025)
"Sven Beckert, founder of Harvard's Program on the Study of Capitalism, has made a profound impact on his field, including his Bancroft-Prize-winning history, Empire of Cotton. That was merely base camp for the epic achievement of his new book. Capitalism, Beckert argues, was born global. Emerging from interconnected nodes in Asia, Africa, and Europe and at first dominated by Arab traders, capitalism rooted itself gradually, persisting for centuries as a vital but limited circulatory system that left most of the world's economic life untouched. But then it burst onto the world scene, as European states and merchants built a powerful alliance that propelled them across the oceans. This, Beckert shows, was modern capitalism's big bang, and its epicenter was the Caribbean. Europeans violently transformed tropical islands into slave labor camps, built with unparalleled efficiency and brutality to produce the world's most valuable commodities. This system, with its hierarchies that haunt us still, provided the lift-off for the even more radical transformations of the Industrial Revolution. Empowered by vast productivity increases, capitalism pulled down old ways of life and expanded its orbit ever further. Gorging on coal and then oil, it erased earlier traditions and crowned itself the defining force of the modern world. This epic drama corresponded at no point to an idealized dream of free markets. All along, state-backed institutions and imperial expansions shaped its dynamics, never more than when the system reached its worst crack-up ever in the two world wars and the Great Depression. In the aftermath, anti-colonial rebellions stripped capitalism of its European flavor to create the multipolar world we live in today. Drawing on archives on five continents, Capitalism decenters the European perspective, locating important modes of agency, resistance, innovation, and ruthless coercion everywhere in the world, including India, Japan, Africa, and the Americas, through to the present with China's rise. Beckert opens the aperture from heads of state to rural cultivators to show that constant struggle is at the core of the capitalist revolution. Despite its dependence on expansion, there always have been, and are still, areas of human life it has yet to reach. By peeling back the layers of capitalism's global history, Beckert exposes the truth of the system that to us now seems simply "natural." It is said that people can more easily imagine the end of the world than the end of capitalism. If there is one ultimate lesson in this extraordinary book, it's how to leave that behind. Capitalism is nothing if not a human invention, and so is the ideology that cloaks itself in a false, timeless universality. Sven Beckert doesn't merely tote up capitalism's debits and credits. He shows us how to look through and beyond our reigning metaphor to imagine a larger world"--